Pengaruh Faktor Fundamental dan Risiko Sistematis Terhadap Expected Return Saham dengan Pendekatan Capital Asset Pricing Model (CAPM) pada Saham Indeks LQ-45 Periode 2018-2022 - Ayantri Biloa; Rizan Machmud; Dewi Indrayani Hamin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aimed to determine the effect of fundamental factors and systematic risk on expected stock returns on LQ-45 Index stocks. Fundamental factors in this study are proxied by: Return On Asset (ROA), Return On Equity (ROE), Price Earning Ratio. While systematic risk is proxied by market risk. This study used secondary data from a population of 45 LQ-45 index companies. In the meantime, the sample in this study were taken using purposive sampling and analyzed using multiple linear regression. The study findings revealed that Return On Asset (ROA) with a value of tcount < ttable (0.074 < 1.664) and significance value (0.941 > 0,05) did not affect the expected return of stocks: further, Return On Equity (ROE) with a value of tcount < ttable (-1.182 < 1.664) and significance value (0.240 > 0.05) did not affect the expected return of stocks. Furthermore, the Price Earning Ratio (PER) with a value of tcount > ttable (2.864 > 1.664) and significance value (0.005 < 0.05) affected the expected return of stocks. Lastly, market risk with a value of tcount < ttable (-6.535 < 1.664) and significance value (0.000 < 0.05) affected the expected return of stock. Simultaneously, Return On Asset (ROA), Return On Equity (ROE), Price Earning Ratio, and market risk affected the expected return return of stocks with a significance value (0.000 < 0.05), where the Fcount > Ftable.